Pengembangan Media Pembelajaran Video Tutorial Manatiang Service Pada Mata Kuliah Penataan Dan Pelayanan Restoran - Ariq Aldera; Yeni Yulianti; Rina Febriana (Syntax Idea)
This research was conducted to determine the development of video tutorial learning media for manatiang service in restaurant management and service courses. This research conducted on Vocational Education in Culinary Arts, State University of Jakarta since June 2022. This research used the Research and Development (R&D) method with the ADDIE development model (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation with data analysis techniques in the form of descriptive percentages. This research was validated by media, material, and language experts. The development of learning media is expressed through validation results by media expert that scores 92% (very good), by material expert that scores 81% (good), and test result obtained from linguists are 82% (good). In the one to one evaluation, the percentage was 94% (very good), in the small group evaluation, the percentage was 94% (very good), in the field group evaluation the percentage was 83% (very good), and in the student responses the percentage was 85% (very good). From the results of the study, it can be concluded that the video tutorial learning media is feasible to use in the learning process.